Voice Assessment in Patients With Obstructive Sleep Apnea Syndrome After Transoral Robotic Surgery - Huang, Hsin-Hsin; Tsao, Chien-Han; Wei, James Cheng-Chung (Frontiers in Surgery, 2021)
Objectives: Removal of part of the tongue base, in combination with uvulopharyngopalatoplasty via transoral robotic surgery (TORS), for treating obstructive sleep apnea syndrome (OSAS) results in enlargement of the oropharynx and hypopharynx and change in the size of the resonance chamber. These procedures may also alter the laryngeal-hyoid bone complex, which is linked to vocal fold tension. Thus, there is the potential for change in phonation and pitch after surgery. Study Design: Prospective, nonrandomized, institutional board-approved study. Methods: From January to August 2018, 15 patients with OSAS receiving TORS underwent voice and pitch sampling. The multi-dimensional voice program (MDVP) was applied to the evaluation of preoperative sound parameters. Highest pitch and lowest pitch were obtained with real-time pitch software, with pitch synchronized to electronic organ or tuner. Subjects also completed the Voice Handicap Index-10 scale (VHI-10), to assess their subjective perception and to detect factors affecting the VHI-10 score. The relevant parameters were analyzed again 3 months after the operation. Results: There was an increase in VHI-10 score 3 months after operation that did not reach statistical significance. There were also no significant differences in sound parameters. Increases in highest pitch (353.18 Hz shift to 387.99 Hz), highest semitone (F5# shift to F5#), lowest pitch (117.45 Hz shift to 131.42 Hz), and lowest semitone (C3 shift to C3) did not reach statistical significance. The increase in the lowest semitone was significantly related to change in VHI-10 score (r = −0.808, P = 0.028). Conclusion: Patients with OSA undergoing TORS showed a negative correlation coefficient over 0.8 with change in VHI-10 score. That is, increase in the lowest semitone after operation correlated with increase in VHI-10 score which may cause perceive changes in subjective pronunciation.